Exploring the Relationship Between Learner Autonomy and Learner Engagement Among EFL Students in Cambodian Universities - Sun, Somara (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: The main aims of this study are to: 1) find out how Cambodian EFL university students perceive learner autonomy and engagement; and 2) find out how these two factors correlate to one another. Methodology: This research adopted a quantitative methods employing cluster sampling for data collection via a bilingual questionnaire in English and Khmer. The data was processed and analyzed using SPSS (Version 23), utilizing both descriptive and inferential statistics, including correlation coefficients, to extract insights from the survey findings. Main Findings: The main findings of this study were: 1) Cambodian EFL university students showed high levels of learner autonomy and engagement, indicating the need for interventions to develop autonomy and create supportive learning environments; and 2) a moderate positive correlation was found between learner autonomy and engagement. Novelty/Originality of this study: The unique aspect of this research is how it identifies the complex correlation between learner autonomy and engagement among EFL university students in Cambodia. High levels of motivation and autonomy were seen, but there were also clear difficulties with self-perceived competence. This comprehensive perspective enhances the existing literature by emphasizing the impact of contextual elements on autonomy and engagement, therefore addressing a gap in current research. Furthermore, the results underline the significance of creating supportive learning environments and the requirement for tailored interventions. These insights have practical implications for educational policy and pedagogical approaches, indicating that educators have to adopt techniques that foster autonomy and offer tailored support to improve learner engagement and optimize resource use.